2016
DOI: 10.1002/lno.10340
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing fish movements between coastal wetland and nearshore habitats of the Great Lakes

Abstract: The use of resources from multiple habitats has been shown to be important to the production of aquatic consumers. To quantify the support of Great Lakes coastal wetland (WL) and nearshore (NS) habitats to yellow perch, we used otolith microchemistry to trace movements between the habitats. WL and NS water and fish samples were collected from lakes Huron and Michigan for water and otolith trace element analysis. Recently deposited otolith‐edge Sr : Ca and Ba : Ca from otoliths were strongly correlated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
(81 reference statements)
3
22
1
2
Order By: Relevance
“…Both STRUCTURE and DAPC grouped yellow perch collected in deep-DRM habitats during autumn with Lake Michigan fish (see Figures 2, 3). Our findings support the hypothesis that some Lake Michigan yellow perch migrate into DRMs in autumn and winter (prior to the spring spawning season), which was further supported by a recent study of otolith microchemistry that found evidence that yellow perch can primarily reside in Lake Michigan and make annual migrations into DRM wetlands (Schoen et al, 2016). 2007).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Both STRUCTURE and DAPC grouped yellow perch collected in deep-DRM habitats during autumn with Lake Michigan fish (see Figures 2, 3). Our findings support the hypothesis that some Lake Michigan yellow perch migrate into DRMs in autumn and winter (prior to the spring spawning season), which was further supported by a recent study of otolith microchemistry that found evidence that yellow perch can primarily reside in Lake Michigan and make annual migrations into DRM wetlands (Schoen et al, 2016). 2007).…”
Section: Discussionsupporting
confidence: 88%
“…Lake Michigan yellow perch (Figures 2, 3). Our finding that littoral-DRM and Lake Michigan yellow perch are distinct genetic stocks is supported by previous otolith and morphology studies that suggested these may be distinct stocks (Parker et al, 2009;Schoen et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations